Stability of cylindrical anisotropic shells under axial pressure in three-dimensional statement - Semenuk, M. P.; Trach, V. M.; Podvornyi, A. V. (КНУБА, 2015)
Approach to the solution of a problem of stability of cylindrical anisotropic shells under the influence of the axial compression, based on use of procedure of Bubnova-Galerkin taking into account boundary conditions on surfaces and end faces of a cylindrical shells and a numerical method of discrete orthogonalization is offered. The problem of stability of a cylindrical shells made of the material which characteristics are described by one plane of elastic symmetry is solved. Dependence of sizes of critical loadings on an angle of rotation of the main directions of elasticity of an initial material relatively curvature designs is investigated. Results are presented in the form of schedules and provided in the table, besides, the analysis is carried out them.
Keywords: cylindrical anisotropic shells; axial pressure; stability of cylindrical shells; 624.074.4